Valoración agronómica y productiva de dos variedades de maní (Arachis hypogaea) con dos dosis de 10-30-10 en la parroquia Pacayacu, cantón Lago Agrio, provincia Sucumbíos - Mariuxi Marisol, Granda Sanchez (2023)
The present research work carried out the "Agronomic and productive evaluation of two varieties of peanuts (Arachis hypogaea) with two doses of 10-30-10 in the Pacayacu parish, Lago Agrio canton, Sucumbíos province." The proposed objectives were: i) Identify the agronomic characteristics of each of the varieties. ii) Determine which of the doses of 10-30-10 obtains the highest productivity. iii) Select the treatment that presents the best agronomic and productive characteristics. iv) Carry out an economic analysis of the cost-benefit ratio. The treatments under study were for the FA two (Peanut varieties) for the FB two (Dose of 10-30-10) and a control (Without fertilization). The Randomized Complete Blocks design (DBCA) was used in a 2x3x3 factorial arrangement. The type of analysis that was carried out was Tukey's test at 5% to compare means of factor A, B and interaction of factors (AXB), correlation analysis and simple linear regression and economic analysis of the benefit-cost relationship. The agronomic components that were evaluated were: Days to seedling emergence (DEP), Percentage of emergence in the field (PEC), Days to flowering (DF), Days to harvest (DC), Number of pods per plant ( NVP), Number of kernels per pod (NGV), Pod length (LV), Peanut weight in pod (PMV), Peanut weight in kernel (PMP), Grain diameter (DG), Grain length (LG) , Weight of 100 grains (PG), Grain moisture (HG), Yield per hectare (R-kg/ha). The statistical results showed that the peanut crop in terms of yield, depended significantly on the varieties and the doses of 10-30-10, the treatment that registered the highest average yield and economic income was: A2B2 (Valencia + 200 kg/ is from 10-30-10).